Analysis and Terminology of Financial Statement items for Highway-Heavy Contractors (Book). - Brooks, William A.; Sterling, Robert R. (The Accounting Review, 1971)
Reviews the book "Analysis and Terminology of Financial Statement Items for Highway-Heavy Contractors," by Felix P. Kollaritsch.